1993
DOI: 10.1073/pnas.90.19.8910
|View full text |Cite
|
Sign up to set email alerts
|

Cell proliferation, DNA repair, and p53 function are not required for programmed death of prostatic glandular cells induced by androgen ablation.

Abstract: Androgen ablation induces programmed death of androgen-dependent prostatic gdular cells, resulting in fragmentation of their genomic DNA and the cells themselves into apoptotic bodies. Twenty percent of prostatic glandular cells undergo programmed death per day between day 2 and 5 after castration. During this same period, <1% of prostatic landular cells enter the S phase of the cell cycle, documenting that >95% of these die in Go. During the programmed death of these Go gadular cells, a futile DNA repir proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0
4

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(105 citation statements)
references
References 31 publications
2
99
0
4
Order By: Relevance
“…24,25 Similarly low proliferation rates (1.3%) have been confirmed in the adult rat prostate. 26 It seems unlikely that proliferation rates alone can account for the far higher tumour incidence in the prostate than that of the epididymis. …”
Section: Cell Proliferation Ratementioning
confidence: 99%
“…24,25 Similarly low proliferation rates (1.3%) have been confirmed in the adult rat prostate. 26 It seems unlikely that proliferation rates alone can account for the far higher tumour incidence in the prostate than that of the epididymis. …”
Section: Cell Proliferation Ratementioning
confidence: 99%
“…Although some reports dispute the importance of p53 in apoptosis induced during certain physiological and pathological states (Berges et al, 1993;Clarke et al, 1993), there is now strong evidence for a positive link between expression of p53 and induction of apoptosis in many other instances (Donehower et al, 1992;Clarke et al, 1993;Lowe et al, 1993;Zhang et al, 1994). As well, wild-type p53, lately recognised as a 'guardian of the genome', regulates DNA replication and repair (Lane, 1992).…”
mentioning
confidence: 99%
“…In the normal rodent prostate, castration results in an induction of apoptosis within the glandular epithelium, with an 80% reduction in prostatic wt/wt by 10 days postcastration. 24 An examination of human prostate specimens after 3 months of androgen ablation also demonstrates an increase in apoptotic activity within both cancerous and noncancerous prostatic tissues. 25,26 Previous studies with androgen-sensitive MPR tumors have demonstrated androgen-sensitive activities in regard to both the growth and expression of apoptosis-related genes in response to castration in vivo.…”
Section: Discussionmentioning
confidence: 99%